Does cessation of community water fluoridation lead to an increase in tooth decay? A systematic review of published studies - McLaren, Lindsay (J Epidemiol Community Health, 2016)
BACKGROUND: Cessation of community water fluoridation (CWF) appears to be occurring with increasing frequency in some regions. Our objective was to comprehensively review published research on the impact of CWF cessation on dental caries. METHODS: We searched 13 multidisciplinary databases. Results were synthesised qualitatively and quantitatively. RESULTS: We identified 15 instances of CWF cessation (‘intervention’) in 13 countries, which covered a broad time frame (1956–2003) and diverse geographical and political/economic contexts. Overall, results were mixed, but pointed more to an increase in caries postcessation than otherwise. For example, of the 9 studies with at least moderate methodological quality based on criteria we developed for this review, 5 showed an increase in caries postcessation. 3 studies did not show an increase in caries postcessation; however, important postcessation changes (eg, implementation of alternative fluoride delivery programmes) and/or large-scale social change may have contributed to those effects. Of the 3 study groupings that permitted quantitative synthesis, 2 showed statistically significant mean overall increase in caries postcessation; however, quantitative synthesis results must be interpreted cautiously. CONCLUSIONS: Overall, the published research points more to an increase in dental caries post-CWF cessation than otherwise. However, the literature is highly diverse and variable in methodological quality. To build this literature, it is important to exploit research opportunities presented by CWF cessation. Remaining knowledge gaps include the impact of CWF cessation on the distribution of dental caries (ie, equitable or not) and understanding the decision-making circumstances around CWF cessation.